Traditional Methods of Islamic Education in Current Learning (Study of Hadits Al-Bukhari and At-Tirmidzi) - Ajrina, Syahida; Hudaya, Hairul (The Future of Education Journal, 2025)
Traditional methods of Islamic education essentially still have an essential role in today's learning that can be optimized through integration with modern technology based methods amidst the development of the times and the increasing needs of students in today's digital era. This research is included in the type of library research that uses a qualitative approach with thematic analysis methods to find traditional methods of Islamic education contained and stated in the hadith of the Prophet Muhammad saw. based on the narrations of Imam al-Bukhari and at-Tirmidzi, and their relevance to today's learning. The results of this study indicate that traditional methods of Islamic education – such as lectures, stories, questions and answers, and demonstrations – have a strong normative basis in the hadits of the Prophet Muhammad saw., as narrated by Imam al-Bukhari in the book Sahih al-Bukhari and Imam at-Tirmidzi in the book Sunan at-Tirmidzi. Traditional methods of Islamic education essentially still have great relevance to be applied in today's learning activities as a foundation underlying the transfer of religious materials delivered by teachers to students. However, the application of traditional methods of Islamic education in today's learning needs to be combined adaptively and integratively with modern technology-based methods in order to meet the needs of students and answer the challenges of the current digital era, so that this not only helps students to understand Islamic teachings theoretically and practically, but also builds active involvement, critical thinking skills, and a more meaningful learning experience for students.